Acute kidney injury among patients undergoing major surgery in a tertiary hospital in Nigeria . (2018)
Background. Acute kidney injury (AKI) is an underreported but major cause of morbidity and mortality among patients undergoing major surgical interventions in sub-Saharan Africa (SSA). Whereas AKI is often seen following major cardiac surgery in high-income countries, a similar spectrum of surgical diseases and interventions is not seen in developing countries. The impacts on surgical outcomes have also not been well characterized in SSA. This study aimed at identifying risk factors, incidence and determinants and short-term outcomes of AKI among patients undergoing major surgery. Methods. This was a cohort study of adult patients undergoing major surgery at the University College Hospital, Ibadan, Nigeria. Data obtained were sociodemographic details, risk factors for AKI, details of surgery, anaesthesia and intraoperative events and short-term outcomes. Blood samples were obtained for pre-operative (pre-op) full blood count, serum electrolytes, blood urea and creatinine (SCr). Post-operatively (Post-op) SCr was determined at 24 h, Day 7 post-op and weekly until each patient was discharged. Results. A total of 219 subjects who had major surgery (86.3% elective) were enrolled. The median age of the patients was 46 (range 18–73) years and 72.6% were females. The surgeries performed were mostly simple mastectomies (37.4%), exploratory laparotomies (22.8%) and total thyroidectomies (16.4%). The incidences of AKI were 18.7% at 24 h and 17.4% at Day 7 post-op, while cumulative AKI incidence was 22.5% at 1-week post-op. Pre-op elevated SCr [odds ratio (OR) 3.86], sepsis (OR 2.69), anaemia (OR 2.91) and duration of surgery >120 min (OR 1.75) were independently associated with AKI. In patient mortality was 20.4% in individuals with AKI and 5.3% in those without AKI (P < 0.01) Conclusion. Peri-operative risk factors for AKI are common among patients undergoing major surgery in SSA hospitals. The cumulative incidence of AKI was high and independently associated with pre-op sepsis, anaemia, pre-existing kidney dysfunction and duration of surgery >120 min